2021
DOI: 10.1108/ijsms-12-2020-0232
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the drivers and consequences of the “awe” emotion in outdoor sports – a study using the latest partial least squares structural equation modeling technique and necessary condition analysis

Abstract: PurposeAwe is an essential post-experience assessment; nevertheless, few studies have discussed its role in the field of outdoor sports or outdoor sports tourism. In this study, the authors aim to examine the effects of awe on participants' satisfaction and behavioral intention by considering the perceived vastness of the natural environment, perceived professionalism, and self-image congruity as drivers.Design/methodology/approachThe authors proposed and empirically tested a research model based on a survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…It proposes NCA as a straightforward method for identifying necessary conditions in data sets. The research findings also illustrate the usefulness of the combination of PLS-SEM and NCA (Liu, Ting, & Ringle, 2021;Liu, Yu, & Damberg, 2021), indicating that it is a favorable method to use in exploratory research to address necessary and sufficient contributions.…”
Section: Theoretical Contributionsmentioning
confidence: 77%
See 1 more Smart Citation
“…It proposes NCA as a straightforward method for identifying necessary conditions in data sets. The research findings also illustrate the usefulness of the combination of PLS-SEM and NCA (Liu, Ting, & Ringle, 2021;Liu, Yu, & Damberg, 2021), indicating that it is a favorable method to use in exploratory research to address necessary and sufficient contributions.…”
Section: Theoretical Contributionsmentioning
confidence: 77%
“…Some users are willing to use a mobile app that they are dissatisfied with and wait for an updated version. In recent years, marketing researchers have adopted the concept of appreciation to measure whether users find what sellers provide is beneficial (Liu, Ting, & Ringle, 2021; Liu, Yu, & Damberg, 2021; Soscia, 2007). As the non‐core features are supplements to banking business, it is expected that users will feel appreciation once they have accrued useful experiences with these relationship investment (Palmatier et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The literature concludes that sufficiency logic and necessity logic are complementary to each other [76]. Thus, the extant business research literature frequently integrates MRA and SEM with NCA to validate proposed hypotheses of sufficiency logic using necessity logic, thereby gaining deeper insights [10][11][12]76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Achi-square test confirmed that respondent groups did not differ significantly, excluding the possibility of non-response bias. We adopted the PLS-SEM method given its suitability for causal-predictive research requiring accurate analysis of mediation effects (Chin et al, 2020;Liu et al, 2021b). In addition, the research model was a reflective-formative second-order model (Becker et al, 2012).…”
Section: Data and Measurementsmentioning
confidence: 99%
“…We adopted the PLS-SEM method given its suitability for causal-predictive research requiring accurate analysis of mediation effects (Chin et al , 2020; Liu et al , 2021b). In addition, the research model was a reflective-formative second-order model (Becker et al , 2012).…”
Section: Data and Measurementsmentioning
confidence: 99%